Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

The role of solvent in lignin hydrothermal liquefaction: its influence on conversion and phenolic monomer selectivity - Dong-Can Lv; Meng-Ru Chen; Yue-Yuan Ye; Duo Wang; Zhi-Min Wang; Yun-Quan Liu (Fuel, 2026)

MiR-324-5p mitigates experimental acute pancreatitis by suppressing Rock2 expression - Qian Chen; Zhao Shen; Qingmei Wang; Ru Jiao; Yehong Liu; Tingting Meng; Yunhui Fei; Caixia Liu (Mammalian Genome, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

From efficient nitrite accumulation to complete collapse: how a microbial community and its antibiotic resistance genes in a nitrification system respond to long-term exposure to ciprofloxacin and copper - Xiao-Yan Fan; Meng-Hao Hao; Jun-Ru Zhao; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Ding-Chang Li (Journal of Water Process Engineering, 2026)

Modification of shrimp tropomyosin properties for improved functional performance: TGase modification and polyphenol-beta-glucan modification - Shiqi Liu; Ru Meng; Kexin Jiang; Yinuo Bai; Zhenxing Li; Lingyi Liu; Jin Wang; Lianliang Liu (Food Chemistry, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Close-to-nature management alters litterfall production and nutrient return in Chinese fir (Cunninghamia lanceolata) plantations across Southern China - Shu-meng Wei; Xiang-teng Chen; Ru-zhen Jiao; Xiong-qing Zhang; Yu-hong Dong (European Journal of Forest Research, 2026)

On-site rapid detection method for Cryptolestes ferrugineus(Coleoptera: Laemophloeidae) based on recombinase polymerase amplification technology - Zhang Ru; Bai Yueliang; Bai Kaixu; Wang Hongjun; Zhao Chao; Yan Lei; Duangsamorn Suthisut; L.V. Jianhua; Zeng Fangfang; Zhang Meng; Bai Chunqi (Journal of Stored Products Research, 2026)

Microbial and metabolomic analyses elucidate the Debaryomyces hansenii-mediated flavor enhancement in dry-aged black pig pork - Ruo-Chun Kao; Meng-Ru Lee; Rung-Jen Tu; Wen-Shyan Chen; Hsiao-Mei Liang; Hsiu-Ming Liu; Hsin-Hui Su; Yen-Po Chen; Yung-Tsung Chen (Food Microbiology, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

A novel sterilization mechanism of cold plasma coupled with low-dose ZnO nanoparticles for food Decontamination: Synergistic reactive species generation and zinc ion release - Hang-Bo Xu; Meng-Ru Du; Zhen Jiao; Pan-Feng Guan; Ruo-Nan Ma (Food Microbiology, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Effects of salinity and fermentation time on the microbial community, flavor, and metabolites of shrimp paste - Jing-ru Chen; Jia-bo Huang; Jing Li; Shi-meng Sun; Peng-fei Jiang (Food Research International, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Study of enhancing analgesic potential of μ-conotoxins from the computational and pharmacological insights - Fan Zhao; Yunxia Liu; Ying Cui; Yushan Ding; Liu Ru; Ting Meng; Hongtao Yang; Yongbo Song (Molecular Diversity, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Highly sensitive ppb-level high-entropy metal oxide gas sensor with temperature-dependent dual-selectivity for Ammonia and Triethylamine - Ru Wang; Guozheng Zhu; Yutong Guo; Yilin Du; Mengran Ran; Yuxin Cao; Hongmin Zhu; Fanli Meng; Yong Zhao (Chemical Engineering Journal, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Formate-strengthened NADH supply in Salinivibrio sp. TGB4 improves polyhydroxyalkanoates production - Yuke Zhang; Meng-Ru Wang; Zheng-Jun Li (World Journal of Microbiology and Biotechnology, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

Coconut shell pyrolysis oil: dual-pathway approach to antioxidants and renewable aromatic biofuels - Ru Sun; Jincheng Zhang; Meng Sun; Xinghua Liu; Dan Qian; Ping Huang (Fuel, 2026)

Naphthalene versus benzene donor in vinyl-linked donor–π–acceptor COFs: Dueling for photocatalytic H2O2 production and water purification - Tong Chen; Meng Xie; Wenli Wu; Xiangfeng Chen; Lingxi Zhao; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Side-chain modified covalent organic frameworks for enhanced visible light photocatalytic degradation of bisphenol A and application in seawater - Tianshuo Liu; Jing Sun; Meng Xie; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Biochar-based oxygen electrocatalysts for advanced Zn-air batteries: Mechanisms, applications, and prospects - Xiao-ru Meng; Shuai Gao; Janusz A. Kozinski; Roger Ruan; Zhen Fang (Chemical Engineering Journal, 2026)

Artificial restoration improved the complexity of the soil microbial co-occurrence network and the resistance of microbial communities to environmental changes in degraded sandy grassland - Wentao Mi; Ru Meng; Weibo Ren; Ting Yuan; Yi Liu; Huijie Han; Jialu Liang; Jinqi Zhang (Agriculture, Ecosystems & Environment, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

OsPP2C03 positively regulates rice drought stress resistance through a non-canonical ABA pathway - Yao Wang; Mingxin Chen; Di Wu; Ru Li; Hanxing Wei; Lingwen Meng; Xuemei Qin; Jinliang Sun; Tianmin Ouyang; Weijian Cen; Rongbai Li; Jijing Luo (Plant Science, 2026)

Beyond electrostatic interaction: Ball milling-induced dominance of pore filling and π-π stacking for methylene blue adsorption on tobacco stem derived activated carbon - Dong-Can Lv; Meng-Ru Chen; Mei-Rong Song; Guang-Ce Jiang; Zhi-Min Wang (Journal of Water Process Engineering, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Fluorescent aptasensor based on magnetic bead–assisted displacement reaction for monitoring vancomycin in plasma - Cheng-Shiuan Hsieh; Hsu-Yun Tsai; Ting-Chien Tsai; Yang-Chun Wang; Yi-Tung Cheng; Jing-Ru Liou; Meng-Yu Liu; Yen-Ling Chen; Chien-Chin Chen (Analytica Chimica Acta, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Isorhamnetin alleviates acute liver injury by blocking ferroptosis - Didi Liu; Yao Zeng; Tao Meng; Yi Ru; Xinru Zhou; Yun Huang; Wei Jiang; Xueting Lang; Ye Tao; Yi Huang (Chemical Engineering Journal, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Elucidating the impact of salt concentration on volatile flavor profiles and microbial dynamics in fermented cockle paste using GC-IMS and high-throughput 16S rDNA sequencing - Shi-meng Sun; Jia-bo Huang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Research International, 2025)

PcSRB cooperates with TLR2 and promotes phagocytosis and antimicrobial peptides expression - Meng-Ke Shan; Jing-Xin Dai; Wen-Ya Li; Jing-Ru Zhu; Gui-Wen Yang; Hui-Ting Yang (Fish & Shellfish Immunology, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Inspired by traditional printing pastes: Green eco-design of phytic acid-modified starch and durable flame-retardant cellulose-based fabrics - Wan-Meng Song; Bao-Hong Wang; Ru-Yu Fan; Yun Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Effects of curcumin on jejunal morphology and intestinal integrity of broiler under heat stress - Ding-Ding Zhang; Meng-Ru Xue; Yu-Ting Liu; Hong-Jie Cui; Ding-Ping Bai (Journal of Thermal Biology, 2025)

Molecular epidemiology and phylogenetic analysis of Echinococcus spp. in the Qinghai-Tibetan Plateau: unraveling genetic evolution in a high-risk region for echinococcosis - Guoyan Zhou; Zhi Li; Xueyong Zhang; Ru Meng; Xiuying Shen; Zhen Zhang; Fuyun Chen; Hong Duo; Yong Fu (Veterinary Research Communications, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

6-Methoxydihydrosanguinarine Suppresses the Proliferation of Non-small Cell Lung Cancer Cells through Elevation of ROS and Activation of IRE1/JNK Signaling - Xiao Qi; Chong Niu; Zi-zheng Zhang; Meng-ru Chen; Feng-ze Wang; Hong-rong Fei (Cell Biochemistry and Biophysics, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Engineering an Ag2Se@PANi core–shell nanozymes – Klebsiella pasteurii hybrid system with enhanced ammonia synthesis - Meng-Xin Zhao; Si-Ru Chen; Bo Hu; Hao Chen; Ya-Xuan Xiao; Ting-Ting Liu; Shan-Shan Hu; Su-Fang Qin; Xuee Wu; Le-Xing You; Feng Zhao (Bioresource Technology, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Mitoquinone mesylate promotes oocyte maturation and subsequent embryonic development by regulating oxidative stress in Tibetan sheep - Bozhen Ji; Chengtu Zhang; Ruolin Zhao; Yifan Pan; Hong Wu; Yongzhong Chen; Ying Wu; Ru Meng; Yingbing Zhang; Yujie Tang; Jianmin Su (Animal Reproduction Science, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

Differential analysis of microorganisms and flavor substances during drying of scallops (Chlamys farreri) based on high-throughput sequencing and headspace gas chromatography-mass spectrometry (HS-GC-MS) - Jing-ru Chen; Jia-bo Huang; Shi-meng Sun; Peng-fei Jiang (Food Bioscience, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Molecular insights into water balance disruption as a pest control strategy for Rhyzopertha dominica (F.) - Yueliang Bai; Guiyao Wang; Ru Zhang; Chunqi Bai; Jianhua Lv; Meng Zhang (Journal of Stored Products Research, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Genomic insights into Marinobacterium sediminicola CGMCC 1.7287T: A polyhydroxyalkanoate-producing bacterium isolated from marine sediment - Meng-Ru Wang; Yuke Zhang; Zheng-Jun Li (Marine Genomics, 2025)

Efficient electrocatalytic degradation of tetracycline using NiCo2O4/MnO2 composite electrode: Synergistic enhancement mechanisms and environmental toxicity assessment - Maoxiang Ru; Kun Lang; Xudong Xiao; Hong Wang; Huiyuan Meng; Baojiang Jiang (Journal of Environmental Chemical Engineering, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Efficient adsorption and separation of glyphosate in aqueous solution by amino-functionalized Poly(glycidyl methacrylate) - Qiyu Meng; Yupei Wang; Meng Rong; Huifang Xing; Ru-An Chi; Congmei Chen; Huizhou Liu; Liangrong Yang (Chemical Engineering Journal, 2025)

Impact of carbon/nitrogen ratio on sequencing batch biofilm reactors initiated with different seed sludges for treating actual mariculture effluents - Xiao-Yan Fan; Shi-Long Zhou; Yanling Yang; Shen-Bin Cao; Yue Niu; Meng-Yuan Zheng; Jun-Ru Zhao (Bioresource Technology, 2025)

Environmentally-Relevant Concentrations of Atrazine Had Minor Impacts on Gut Microbiota and Liver Metabolite in Juvenile Turtles - Huo-Bin Tang; Xin-Ru Qian; Wan-Qiu Yang; Jia-Meng Yang; Jin-Hui Zhang; Hong-Liang Lu (Archives of Environmental Contamination and Toxicology, 2025)

Evolutionary Analysis of Hypoderma Pantholopsum in Tibetan Antelopes on the Qinghai–Tibetan Plateau - Fan Zhang; Haining Zhang; Zhi Li; Ru Meng; Peiling Ye; Yong Fu (Acta Parasitologica, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Prediction of the potential dispersal corridors for Gaoligong hoolock gibbon in northern Yingjiang, Yunnan, China - Yong-liang Zhu; Meng-ling Xu; Li-xiang Zhang; Peng Li; Bao Jin; An-ru Zuo; Xue-long Jiang; Zhen-hua Guan (Journal for Nature Conservation, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Amorphous Solid Dispersions of Glycyrrhetinic Acid: Using Soluplus, PVP, and PVPVA as the Polymer Matrix to Enhance Solubility, Bioavailability, and Stability - Meng-yu Zhao; Xian-bao Shi; Jin-hua Chang; Ru-xing Wang; Jian-yu Zhou; Pei Liu (AAPS PharmSciTech, 2024)

Mechanistic insights into the efficient activation of peracetic acid by mackinawite (FeS) for diclofenac degradation under near-neutral conditions: Multiple identification and contribution of non-radicals - Yao-Feng Gao; Yan-Ping Duan; Yu-Ru Chen; Yuan-Hua Jia; Yao-Jen Tu; Chao-Meng Dai (Chemical Engineering Journal, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Effects of dielectric barrier discharge cold plasma treatment on quality maintenance, energy and γ-aminobutyric acid accumulation of fresh-cut carrots - Wanli You; Xianwei Meng; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Control, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Regulating N-doped biochar with Fe-Mo heterojunctions as cathode in long-life zinc-air battery - Xiao-ru Meng; Shuai Gao; Nianxi Liu; Pei-dong Wu; Zhen Fang (Chemical Engineering Journal, 2024)

Role of Nitrogen-doping in porous carbon for enlarging working voltage window of aqueous supercapacitors in neutral electrolyte - Shao-Wen Xu; Jing-Xuan Dai; Meng-Die Wang; Ru-Yue Zhu; Yong-Qing Zhao (Chemical Engineering Journal, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Seed priming using different agents can alleviate salt stress in kenaf (Hibiscus cannabinus L.) by activating antioxidant system and related genes expression - Renxue Li; Dengjie Luo; Muzammal Rehman; Xin Li; Caijin Wang; Shan Cao; Guofeng Xu; Meng Wang; Canni Chen; Jingzhi Nie; Ru Li; Tao Chen; et al. (Physiology and Molecular Biology of Plants, 2024)

One new 12, 8-guaianolide sesquiterpene lactone with antihyperglycemic activity from the roots of Cichorium intybus - Xiu-hua Meng; Yin-an Pan; Han Lv; Xiao-qin Ding; De-quan Yin; Ya-nan Gai; Guan-ting Niu; Bing-ru Ren; Xiao-guo Qian; Jian Chen (Natural Product Research, 2024)

Unraveling the characteristics of microplastics in agricultural soils upon long-term organic fertilizer application: A comprehensive study using diversity indices - Sen Guo; Guangmin Xiao; Yanhua Chen; Jiajia Zhang; Baogui Zhang; Shuhua Ru; Meng Zhao (Chemosphere, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

TNFAIP1 promotes macrophage lipid accumulation and accelerates the development of atherosclerosis through the LEENE/FoxO1/ABCA1 pathway - Can Xu; Jun Meng; Xiao-Hua Yu; Ru-Jing Wang; Mei-Ling Li; Shan-Hui Yin; Gang Wang (Journal of Physiology and Biochemistry, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Hydroxyl-containing triazine-based conjugated microporous polymers for solid phase extraction of fluoroquinolone antibiotics in the environment and food samples - Lu-Shu Meng; Xiao-Li Wang; Xia Wang; Lei Ji; Lei-Lei Wang; Ya-Qi Cai; Ru-Song Zhao (Food Chemistry, 2024)

Prenatal exposure to fenvalerate causes depressive-like behavior in adulthood by inhibiting brain-derived 5-HT synthesis - Hui-Min Zhu; Bo Wang; Tao Wang; Jing Shao; Hui-Ru Chen; Chi Zhang; Li-Hua Xu; Jing-Jing Li; Min Wang; De-Xiang Xu; Xiu-Hong Meng (Environmental Pollution, 2024)

Screening of Strain from Reconstituted Sheet Tobacco Making High-Yield Enzyme and Aroma - Chun-Xue Yang; Deng Zhang; Hui Ma; Xiao-Meng Guo; Na Yan; Xue-Ting Deng; Xiang-Ru Liao; Zheng-Bing Guan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Genome-wide identification of the SAUR gene family and screening for SmSAURs involved in root development in Salvia miltiorrhiza - Wei Wang; Yuwei Zheng; Lin Qiu; Dongfeng Yang; Ziyang Zhao; Yuanyuan Gao; Ru Meng; Hongguang Zhao; Shuncang Zhang (Plant Cell Reports, 2024)

Efficient activation of peracetic acid by cobalt modified nitrogen-doped carbon nanotubes for drugs degradation: Performance and mechanism insight - Mingya Yao; Shuofeng Zhang; Meng Xie; Lingxi Zhao; Ru-Song Zhao (Chemosphere, 2024)

Di- and tri-methylation of histone H3K36 play distinct roles in DNA double-strand break repair - Runfa Chen; Meng-Jie Zhao; Yu-Min Li; Ao-Hui Liu; Ru-Xin Wang; Yu-Chao Mei; Xuefeng Chen; Hai-Ning Du (Science China Life Sciences, 2024)

A clean label O/W pickering emulsion stabilized by pectin-containing lignocellulosic nanofibrils isolated from apple pomace - Chi Zhang; Tian Gong; Shan Qiang; Xiao Yu Wang; Xiao Ru Wang; Shuai Zhang; Yong Hong Meng (Food Hydrocolloids, 2024)

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Comprehensive evaluation of antibiotics pollution the Yangtze River basin, China: Emission, multimedia fate and risk assessment - Yu-Ru Chen; Yan-Ping Duan; Zhi-Bo Zhang; Yao-Feng Gao; Chao-Meng Dai; Yao-Jen Tu; Jun Gao (Journal of Hazardous Materials, 2024)

Physiological, transcriptome and gene functional analysis provide novel sights into cadmium accumulation and tolerance mechanisms in kenaf - Shan Cao; Meng Wang; Jiao Pan; Dengjie Luo; Samavia Mubeen; Caijin Wang; Jiao Yue; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Journal of Environmental Sciences, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Formation of extracellular polymeric substances corona on TiO2 nanoparticles: Roles of crystalline phase and exposed facets - Tingting Du; Ru Meng; Liwen Qian; Ziyan Wang; Tong Li; Lijun Wu (Water Research, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

Antioxidant CeO2 doped with carbon dots enhance ammonia production by an electroactive Azospirillum humicireducens SgZ-5T - Gao-Kai Wu; Meng-Xin Zhao; Si-Ru Chen; Yi-Nan Sun; Su-Fang Qin; Ai-Jun Wang; Qun-Feng Ye; Hend Alwathnani; Le-Xing You; Christopher Rensing (Chemosphere, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

Feasibility of Wave Simulation in Typhoon Using WAVEWATCH-III Forced by Remote-Sensed Wind - Ru Yao; Weizeng Shao; Youguang Zhang; Meng Wei; Song Hu; Juncheng Zuo (Journal of Marine Science and Engineering, 2023)
The purpose of our work was to assess the feasibility of hindcasting waves using WAVEWATCH-III (WW3) in a typhoon by assembling winds from multiple remote-sensed products. During the typhoon season in 2021–2022, the swath wind products in the Western Pacific Ocean were collected from scatterometers and radiometers. Cyclonic winds with a spatial resolution of 0.125° at intervals of 6 h were obtained by assembling the remote-sensed winds from those satellites. The maximum wind speeds, Vmax, were verified using the reanalysis data from the National Hurricane Center (NHC), yielding a root-mean-squared error (RMSE) of 4.79 m/s and a scatter index (SI) value of 0.2. The simulated wave spectrum was compared with the measurements from Surface Waves Investigation and Monitoring (SWIM) carried out on the Chinese–French Oceanography Satellite (CFOSAT), yielding a correlation coefficient (Cor) of 0.80, squared error (Err) of 0.49, RMSE of significant wave height (SWH) of 0.48 m with an SI of 0.25, and an RMSE of the peak wave period (PWP) of 0.95 s with an SI of 0.10. The bias of wave (WW3 minus European Centre for Medium-Range Weather Forecasts (ECMWFs) reanalysis (ERA-5)) concerning the bias of wind (assembling minus ERA-5) showed that the WW3-simulated SWH with the assembling wind forcing was significantly higher than that with the ERA-5 wind forcing. Moreover, the bias of SWH gradually increased with an increasing bias of wind speed; i.e., the bias of SWH increased up to 4 m as the bias of wind speed reached 30 m/s. It was concluded that the assembling wind from multiple scatterometers and radiometers is a promising source for wave simulations via WW3 in typhoons.

Harnessing microbial phylum-specific molecular markers for assessment of environmental estrogen degradation - Tsun-Hsien Hsiao; Po-Hao Chen; Po-Hsiang Wang; Guo-Jie Brandon-Mong; Chen-Wei Li; Masae Horinouchi; Toshiaki Hayashi; Wael Ismail; Menghsiao Meng; Yi-Lung Chen; Yin-Ru Chiang (Science of The Total Environment, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Effects of photochlorination on the physicochemical transformation of polystyrene nanoplastics: Mechanism and environmental fate - Tingting Du; Song Shao; Liwen Qian; Ru Meng; Tong Li; Lijun Wu; Yao Li (Water Research, 2023)

Low-carbon development pathways for provincial-level thermal power plants in China by mid-century - Ru Li; Bao-Jun Tang; Meng Shen; Chen Zhang (Journal of Environmental Management, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Zinc supplementation promotes oocyte maturation and subsequent embryonic development in sheep - Yupei Yao; Yujie Tang; Haoqiang Qin; Ru Meng; Chengtu Zhang; Yingbing Zhang; Ying Yang; Peipei Qiao; Jun Liu; Jianmin Su (Theriogenology, 2023)

Inhibition of ecdysone receptor (DcEcR) and ultraspiracle (DcUSP) expression in Diaphorina citri increased susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Xi Wang; Yu-Jing Wei; Ling Zhong; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Inhibitory effect of Portulaca oleracea L. aqueous extract and juice on NLRP3 inflammasome activation in an ulcerative colitis mouse model - Yi-meng Fan; Yuan-yuan Wei; Hui-ru Wang; Yu-Ga; Yan-nan Zhang; Zhihui Hao (Environmental Science and Pollution Research, 2023)

Gestational 1-nitropyrene exposure causes anxiety-like behavior partially by altering hippocampal epigenetic reprogramming of synaptic plasticity in male adult offspring - Bo Wang; Ting Zhao; Xiao-Xi Chen; Yan-Yan Zhu; Xue Lu; Qing-Hua Qian; Hui-Ru Chen; Xiu-Hong Meng; Hua Wang; Wei Wei; De-Xiang Xu (Journal of Hazardous Materials, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Automatic back analysis of mechanical parameters using block discrete element method and PSO algorithm - Hang-Sheng Ma; Huan-Ling Wang; Ru-Bin Wang; Qing-Xiang Meng; Lan-Lan Yang (European Journal of Environmental and Civil Engineering, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Effects of H2O2 acclimation on the growth, polysaccharide production and tolerance performance of Nostoc flagelliforme - Shu-ting Liu; Shuai Wang; Na Han; Meng-yuan Li; Jian Li; Yan-ru Li; Shi-ru Jia; Pei-pei Han (Algal Research, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

COSEν: A collective oscillation simulation engine for neutrinos - Manu George; Chun-Yu Lin; Meng-Ru Wu; Tony G. Liu; Zewei Xiong (Computer Physics Communications, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

Insights into the development of pentylenetetrazole-induced epileptic seizures from dynamic metabolomic changes - Xue Zhao; Peixuan Cheng; Ru Xu; Kaili Meng; Sha Liao; Pu Jia; Xiaohui Zheng; Chaoni Xiao (Metabolic Brain Disease, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

First report of Capsicum frutescens endornavirus 1 infecting pepper in China - Ming-xia Gong; Hu Zhao; Xing Wu; Meng Wang; Zeng-jing Zhao; Zhi He; Ru-kui Huang; Jing-ping Sun; Ri-sheng Wang (Journal of Plant Pathology, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Bacterial Community Structure and Diversity in the Aqueous Environment of Shihou Lake and its Relationship with Environmental Factors - Ru Deng; Xi Chen; Li-Ping Qiu; Jia-Zhang Chen; Shun-Long Meng (Indian Journal of Microbiology, 2021)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Epigenetics in psoriasis: perspective of DNA methylation - Ying Luo; Keshen Qu; Le Kuai; Yi Ru; Keke Huang; Xiaoning Yan; Meng Xing (Molecular Genetics and Genomics, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Re-use of wasted sludge to treat industrial pollutants - Ru Wang; Li-ping Yu; Bibi Saima Zeb; Lin-jie Yuan; Meng-yu Liu; Lin-jiang Yuan (Water, Air, & Soil Pollution, 2021)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Comparative Variations of Extractive Nitrogenous Components and Quality in Fresh Muscle and Dried Product of Rabbitfish ( Siganus fuscescens ) in Taiwan - Yu-Ru Huang; Wan-Yi Huang; Hsiao-Chin Jen; Bi-Yu Liu; Ken-Meng Huang; Deng Fwu Hwang (Journal of Aquatic Food Product Technology, 2020)

Testing and constitutive modelling of the mechanical behaviours of gravelly soil material - Jiu-Chang Zhang; Yue Li; Bo Xu; Qin-Xiang Meng; Qiang Zhang; Ru-Bin Wang (Arabian Journal of Geosciences, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Selenium (Se) Does Not Reduce Cadmium (Cd) Uptake and Translocation in Rice (Oryza sativa L.) in Naturally Occurred Se-Rich Paddy Fields with a High Geological Background of Cd - Bei-Bei Yang; Cheng Yang; Zong-Yuan Shao; Hao Wang; Shu-Ting Zan; Meng Zhu; Shou-Biao Zhou; Ru-Yi Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Molecular cloning, antiserum preparation and expression analysis during head regeneration of $$\upalpha $$ α -crystallin type heat shock protein in Hydra vulgaris - Wen-Fang Dong; Hang Zhang; Ru-Meng Wang; Hong-Chun Pan (Journal of Genetics, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

CAT and MDH improve the germination and alleviate the oxidative stress of cryopreserved Paeonia and Magnolia pollen - Meng Xue Jia; Xue Ru Jiang; Jin Xu; Wei Di; Yin Shi; Yan Liu (Acta Physiologiae Plantarum, 2018)

ROS-induced oxidative stress is closely related to pollen deterioration following cryopreservation - Meng Xue Jia; Yin Shi; Wei Di; Xue Ru Jiang; Jin Xu; Yan Liu (In Vitro Cellular & Developmental Biology - Plant, 2017)

The pharmacological activities and mechanisms of artemisinin and its derivatives: a systematic review - Yi-Fei Dai; Wei-Wei Zhou; Jing Meng; Xin-Liang Du; Yun-Peng Sui; Li Dai; Peng-Qian Wang; Hai-Ru Huo; Feng Sui (Medicinal Chemistry Research, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

Investigation on time-dependent behaviour and long-term stability of underground water-sealed cavern - Huan-ling Wang; Wei-ya Xu; Long Yan; Qing-xiang Meng; Ru-bin Wang; Hai-bin Zhao; Wei-chau Xie (European Journal of Environmental and Civil Engineering, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)

Efficient secretory production of CotA-laccase and its application in the decolorization and detoxification of industrial textile wastewater - Zheng-Bing Guan; Yan Shui; Chen-Meng Song; Ning Zhang; Yu-Jie Cai; Xiang-Ru Liao (Environmental Science and Pollution Research, 2015)

Antitumor Activity of DMAKO-05, a Novel Shikonin Derivative, and Its Metabolism in Rat Liver Microsome - Xu Zhang; Ru-Bing Wang; Wen Zhou; Sui Xiao; Qing-Qing Meng; Shao-Shun Li (AAPS PharmSciTech, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Experimental Evaluation of the Sustainability of Dwarf Bamboo (Pseudosasa usawai) Sprout-Harvesting Practices in Yangminshan National Park, Taiwan - Chi-Cheng Liao; Chi-Ru Chang; Meng-Ting Hsu; Wak-Kim Poo (Environmental Management, 2014)

Study on phosphorus loadings in ten natural and agricultural watersheds in subtropical region of China - Yuyuan Li; Cen Meng; Ru Gao; Wen Yang; Junxia Jiao; Yong Li; Yi Wang; Jinshui Wu (Environmental Monitoring and Assessment, 2014)

Photodegradation of the antimicrobial triclocarban in aqueous systems under ultraviolet radiation - Shi-Ling Ding; Xi-Kui Wang; Wen-Qiang Jiang; Xia Meng; Ru-Song Zhao; Chen Wang; Xia Wang (Environmental Science and Pollution Research, 2013)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Sociodemographic characteristics and risk factor analysis of Demodex infestation (Acari: Demodicidae) - Ya-e Zhao; Na Guo; Meng Xun; Ji-ru Xu; Mei Wang; Duo-lao Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Biotreatment of oily wastewater by rhamnolipids in aerated active sludge system - Hong-zi Zhang; Xu-wei Long; Ru-yi Sha; Guo-liang Zhang; Qin Meng (Journal of Zhejiang University-SCIENCE B, 2009)

Myosin light chain kinase modulates hypotonicity-induced Ca2+ entry and Cl– channel activity in human cervical cancer cells - Meng-Ru Shen; Paola Furla; Cheng-Yang Chou; Clive J. Ellory (Pflügers Archiv - European Journal of Physiology, 2002)

Swelling-activated taurine and K + transport in human cervical cancer cells: association with cell cycle progression - Meng-Ru Shen; Cheng-Yang Chou; J. Clive Ellory (Pflügers Archiv - European Journal of Physiology, 2001)

Effects of RNA editing on the coxI evolution and phylogeny reconstruction - Alfred E. Szmidt; Meng-Zhu Lu; Xiao-Ru Wang (Euphytica, 2001)

Volume-sensitive KCl cotransport associated with human cervical carcinogenesis - Meng-Ru Shen; Cheng-Yang Chou; J. Clive Ellory (Pflügers Archiv - European Journal of Physiology, 2000)

Rna editing in gymnosperms and its impact on the evolution of the mitochondrial coxI gene - Meng-Zhu Lu; Alfred E. Szmidt; Xiao-Ru Wang (Plant Molecular Biology, 1998)